An Analysis of Adverbial Clauses of Time in “The Good Girl’s Bad Boys: The Good, The Bad, and The Bullied” Story - Elok Nur Affah Al Akromi (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
Reading is one of the most popular hobbies, enjoyed by millions of people worldwide. As the world keeps developing, the amount of new discoveries keeps rising, including media for reading. Among them is Wattpad, which is a new platform for reading and one of them is the Wattpad. This study aims to identify the patterns, functions, and stylistic choices of adverbial clauses within the text. The research uses the qualitative approach with content analysis method, complimented by descriptive design. The reseach used the qualitative and quantitative approaches. The results show that even a fictional, digital story like